POLLEN MICROMORPHOLOGY OF FOUR Onobrychis SPECIES (Fabaceae) FROM THE KURDISTAN REGION OF IRAQ - Darweesh, Chareen; Salih Abdulrahman, Shamiran; Jassim Muhammed , Jotyar (Science Journal of University of Zakho, 2025)
Polleniferous materials of four Onobrychis species were used in this study. Two different microscopes and one-way ANOVA analysis were applied. The pollen grains were tricolpate, isopolar, and consistently radially symmetrical. The value of the polar axis/equatorial diameter ranged from prolate to perprolate, which were categorized as tiny or medium in size. Exine sculpture patterns varied significantly when scanning electron microscopy was used: Onobrychis megataphora, O. crista-galli, and O. caput-galli have reticulate patterns; O. galegifolia has micro-reticulate perforates. The pollen morphology of O. caput-galli was noticeably perprolate due to its maximum polar axis/equatorial diameter value (2.02 µm). The O. crista-galli had the lowest polar axis/equatorial diameter value (1.37 µm), showing its prolate pollen morphology. A one-way ANOVA analysis revealed significant differences (P < 0.05) in the morphological features of polar length and equatorial diameter. The O. megataphros was primarily circular to ovoid-triangular in form, and O. caput-galli had a triangular outline. The two remaining species had circular shapes in polar view. In equatorial view, two species had elliptic-elongated shapes, while others had rectangular-obtuse outlines. Thus, these micromorphological dissimilarities indicate variations among taxa, and they can be used as taxonomic characters to identify and delimit Onobrychis species